The analysis of disperse and elemental composition of dust from drobestry installations of foundry at the production of construction structures for altitude buildings - Ivanova Irina (E3S Web of Conferences, 2018)
In the production of building structures for high-rise buildings, the dangerous and harmful factors of foundry production include high concentrations of dust and harmful gases released at various stages of the process. Disperse and elemental compositions of dust determine the hygienic state of the working area of the foundry. According to experts, the presence of dust of less than 10 microns in size in the air increases the danger of getting occupational diseases, such as pneumoconiosis (silicosis), bronchitis, dermatitis, conjunctivitis. The determination of the granulometric composition of the powder sample provided was carried out by the laser diffraction method realized on a laser particle analyzer Fritsch NanoTec «ANALISETTE 22».